MODEL PERSON-ORGANIZATION FIT (P-O FIT MODEL) TERHADAP KEPUASAN KERJA, KOMITMEN ORGANISASIONAL DAN KINERJA KARYAWAN - Sih Darmi Astuti (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2010)
This research propose to examine the effect of person-organization fit on jobsatisfaction, organizational commitment, and employee performance. One hundred and fifty ninerespondents from Laksana Company, which produce autobus, located in Ungaran, Semarang,completed 42 items self-reported measures. The data collected survey method and questionnairesdistributed to respondent who have minimum three years in that job. The statistic method usedwas Structural Equation Modeling (SEM) assisted by application of AMOS 5.0 version. Asexpected, result indicated that the perception of person-organization fit has a positive effects onjob satisfaction, organizational commitment, and employee performance, while job satisfactionhave a positive effect on organizational commitment and employee performance, and thenorganizational commitment has a positive effect on employee performance. Furthermore, resultsshow that organizational commitment (especially affective commitment and continuancecommitment) have a stronger effect on employee performance than job satisfaction and personorganizationfit.Keywords: person-organization fit, job satisfaction, organizational commitment and employeeperformance